2009
DOI: 10.1016/j.jmb.2009.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ligand Binding Affinity with Alchemical Free Energy Methods in a Polar Model Binding Site

Abstract: We present a combined experimental and modeling study of organic ligand molecules binding to a slightly polar engineered cavity site in T4 lysozyme (L99A/M102Q). For modeling, we computed alchemical absolute binding free energies. These were blind tests performed prospectively on 13 diverse, previously untested candidate ligand molecules. We predicted that eight compounds would bind to the cavity and five would not; 11 of 13 predictions were correct at this level. The RMS error to the measurable absolute bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
246
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(261 citation statements)
references
References 45 publications
2
246
0
5
Order By: Relevance
“…Formed in the hydrophobic core of the protein, the resulting 150-Å 3 cavity is sequestered from solvent and is almost entirely apolar. Seminal studies by Matthews and colleagues demonstrated that this cavity can bind aryl hydrocarbons (20,21), and since then the cavity and related mutants have become model systems for ligand recognition (22)(23)(24)(25)(26)(27)(28)(29). Contributing to this status has been the commercial availability of thousands of likely ligands, many closely related to one another.…”
mentioning
confidence: 99%
“…Formed in the hydrophobic core of the protein, the resulting 150-Å 3 cavity is sequestered from solvent and is almost entirely apolar. Seminal studies by Matthews and colleagues demonstrated that this cavity can bind aryl hydrocarbons (20,21), and since then the cavity and related mutants have become model systems for ligand recognition (22)(23)(24)(25)(26)(27)(28)(29). Contributing to this status has been the commercial availability of thousands of likely ligands, many closely related to one another.…”
mentioning
confidence: 99%
“…These orientational restraints are commonly applied in absolute binding free energy calculations. 22,23,12,24 In essence, two absolute binding calculations are performed at once, in different directions, and overlapping in the middle. The path (representing transformation G site in Figure 1) is shown in Figure 2.…”
Section: The Separated Topologies Methodsmentioning
confidence: 99%
“…Even very similar ligands in simple binding sites often adopt different orientations and the kinetic barriers between orientations can be significant enough that ligands will not reorient during relative free energy calculations using the standard approaches reviewed earlier (cf. the difference between relative transformations with phenol and catechol in Boyce et al (2009) 12 ). Also, even if ligands eventually reorient, this step can be rate limiting to converging the relative binding free energy, meaning that using a cycle which does not require reorientation will be more efficient.…”
Section: The Separated Topologies Methodsmentioning
confidence: 99%
See 2 more Smart Citations